LOCUS OF CONTROL AS A DETERMINANT OF AGGRESSIVENESS IN INTELLECTUALLY GIFTED ADOLESCENTS - T. A. Voronova; S. V. Dubrovina; Ju. V. Chepurko (Obrazovanie i Nauka, 2018)
Introduction. At the present time, a state and a social request for the guidance of gifted children and teenagers, seen as comprising the primary intellectual potential of a developing society, is being articulated. As a general rule, giftedness is an adjunct to nervousness, extreme sensitivity, internal contradiction and low resistance to stress. These mental disorders may prevent a young person from forming of the proper picture of the world and developing capabilities of forming confidential and harmonious relationships. In this regard, it is necessary to identify appropriate approaches and means for ameliorating the maladaptive behaviour of gifted pupils.The aim of the research was to find out to what extent the personal locus of control determines aggressive and destructive behaviour on the part of intelligently gifted teenagers. Methodology and research methods. The research was performed on the basis of systematic and person-oriented approaches to studying the individual characteristics of students. The types of locus of personal control were determined using J. Rotter’s methodology as adapted by E. F. Vazhin, S. A. Golynkina and A. M. Etkind. As diagnostic tools, E. P. Ilyin and P. A. Kovalyov’s measurement procedure and the Buss-Durkee questionnaire were used to estimate the level of personal aggression and proneness to conflict. Results were subjected to comparative and statistical analysis using the U-Kruskal – Wallis test allowing the authors to establish the average indicator values of various pupil categories participated in the research. Results and scientific novelty. To identify intelligently gifted teenagers, the authors applied a comprehensive programme, which included the methods of psycho-diagnostics, expert estimates of teachers and parents, observation and conversations. Consequently, respondents were divided into four differentiated groups: intelligently gifted externalisers, intelligently gifted internalisers, mediumintelligence externalisers, and medium-intelligence internalisers. In the course of diagnostics, it was established that domination of the external or internal locus of control causes the specifics of aggressive behaviour among intelligently gifted teenagers and their peers having an average level of intellectual development. Statistically significant differences in indicators such as physical aggression, irascibility, irritability and irritation were revealed. An internal locus of control in a gifted person reduces physical aggression and irritability. Gifted externalisers are more inclined to use physical force in conflicts. This group is also characterized by a lack of emotional self-control, irascibility, fieriness of temper, instability, intolerance, oppositional moods and remonstrative behaviour – from passive resistance to active fighting against norms and laws which they believe to be inappropriate for them.The authors concluded that intellectually gifted teenagers with an external locus of control are in the category of teenagers-at-risk in social and psychological adaptation; therefore, they require more attention and psychological assistance. The organization of psychological and pedagogical guidance to pupils will help minimize conflicts between participants (school students and teachers) in the educational process.Practical significance. The research results can be used as informative and reflexive material by educational psychologists and teachers working with intelligently gifted children and teenagers.